2010
DOI: 10.1182/blood-2010-03-276519
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency type I/II mutational shifts between diagnosis and relapse are associated with outcome in pediatric AML: implications for personalized medicine

Abstract: Although virtually all pediatric patients with acute myeloid leukemia (AML) achieve a complete remission after initial induction therapy, 30%-40% of patients will encounter a relapse and have a dismal prognosis. To prevent relapses, personalized treatment strategies are currently being developed, which target specific molecular aberrations. To determine relevance of established AML type I/II mutations that may serve as therapeutic targets, we assessed frequencies of these mutations and their persistence during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 48 publications
3
63
1
Order By: Relevance
“…Studying pediatric and adult AML patients, we have previously shown that shifts in specific type I/ II molecular aberrations occur frequently in between diagnosis and relapse. 15,16 Here we explored the hypothesis that mutational shifts can be explained by selection and subsequent expansion of leukemic cells from a minor subpopulation of an oligoclonal leukemia-initiating fraction at initial diagnosis, analogous to what has been reported for ALL. 32 We analyzed and compared the mutational profiles of sorted subfractions and proved oligoclonality at initial diagnosis in six out of seven relapsed AML patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying pediatric and adult AML patients, we have previously shown that shifts in specific type I/ II molecular aberrations occur frequently in between diagnosis and relapse. 15,16 Here we explored the hypothesis that mutational shifts can be explained by selection and subsequent expansion of leukemic cells from a minor subpopulation of an oligoclonal leukemia-initiating fraction at initial diagnosis, analogous to what has been reported for ALL. 32 We analyzed and compared the mutational profiles of sorted subfractions and proved oligoclonality at initial diagnosis in six out of seven relapsed AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 --19 Regarding mutational shifts, both gains and losses of mutations occur, except for WT1, in which only an apparent gain of mutations was observed. 16,20 Moreover, we showed that the mutational shifts in FLT3/ITD, RAS and WT1 are associated with both the time to relapse (TTR) and overall survival. 16 Differences in genetic aberrations between diagnosis and relapse may be explained by: (1) Continuous accumulation of secondary mutations in (pre-) leukemia initiating cells (LICs), (2) Selection and expansion of a minor, initially undetected clone, from an oligoclonal compartment of leukemia initiating cells at the time of initial presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable analyses of mutation status between the diagnosis and the relapse of AML revealed the loss of class II mutations, such as NPM1 and CEBPA mutations, at the relapse. In contrast, epigenetic modifier mutations are stably identified during the disease progression of AML, while they are frequently acquired at the later stage of MPN, suggesting their multiple oncogenic potency not only for the initiation, but also for progression in myeloid malignancies [22][23][24].…”
Section: Interaction Of Genetic Alterations In Amlmentioning
confidence: 99%
“…In vitro and in vivo studies suggest that this class of mutations augments proliferation and survival signals, but does not induce AML but MPN by itself in murine model [21]. Clinically, this type of mutations sometimes emerge or occasionally disappear during clinical course of AML and MDS [22][23][24]. These mutations (so-called class I mutation) are mutually exclusive but not so strictly as the above class of mutations (class II mutation), and not related with AML subtypes except for the preference of KIT mutation to CBF leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…However, the newly discovered molecular mutations, such as NPM1 or GATA1 mutations, may also be suitable MRD-targets. (Pine, et al 2005 Some of these targets, such as FLT3 mutations, may not be stable between diagnosis and relapse, and this may result in false-negative results (Bachas, et al 2010), which may also occur in flowcytometry based MRD assessment due to immunophenotypic shifts. Another important issue is the frequency of required sampling post-treatment, as leukemias may differ in the lag-time between molecular and overt relapse, which appears to be translocation/molecular marker dependent.…”
Section: Minimal Residual Diseasementioning
confidence: 99%